2018
DOI: 10.3389/fpubh.2018.00044
|View full text |Cite
|
Sign up to set email alerts
|

A Discussion of Virtual Reality As a New Tool for Training Healthcare Professionals

Abstract: BackgroundVirtual reality technology is an exciting and emerging field with vast applications. Our study sets out the viewpoint that virtual reality software could be a new focus of direction in the development of training tools in medical education. We carried out a panel discussion at the Center for Behavior Change 3rd Annual Conference, prompted by the study, “The Responses of Medical General Practitioners to Unreasonable Patient Demand for Antibiotics––A Study of Medical Ethics Using Immersive Virtual Real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…The affective component of learning has been described as one of the four key criteria for simulation-based learning, which is centered on the learners' needs and for which motivation and self-efficacy are key concepts (60) . With this in mind, many VR simulators allow participants to replay their session, helping them recognize and analyze both their interactions and their emotions (61) . The emotional impact of VR simulation on self-efficacy is emphasized and appreciated by trainees (44) , as well as the opportunity provided by some scenarios to communicate with other disciplines before any clinical practice (47) or to experience human interactions in problematic environments (51) .…”
Section: Discussionmentioning
confidence: 99%
“…The affective component of learning has been described as one of the four key criteria for simulation-based learning, which is centered on the learners' needs and for which motivation and self-efficacy are key concepts (60) . With this in mind, many VR simulators allow participants to replay their session, helping them recognize and analyze both their interactions and their emotions (61) . The emotional impact of VR simulation on self-efficacy is emphasized and appreciated by trainees (44) , as well as the opportunity provided by some scenarios to communicate with other disciplines before any clinical practice (47) or to experience human interactions in problematic environments (51) .…”
Section: Discussionmentioning
confidence: 99%
“…While promising telemedicine opportunities are present, to successfully implement telemedicine in cancer care and primary care, education and training should be made available to both patients and health care practitioners [ 118 ]. Research conducted by Stanford University shows that 47% of physicians and 73% of medical students surveyed indicated that they are considering taking additional courses to better prepare for innovations in health care (eg, data science, AI) [ 127 ].…”
Section: Opportunities and Solutionsmentioning
confidence: 99%
“…Many studies from the past decade found VR to be efficacious, easy to use, safe, and contributing to training capabilities and decision making in several fields like healthcare ( Fertleman et al, 2018 ; Walsh et al, 2018 ), education ( Freina and Ott, 2015 ), and industry ( Sportillo et al, 2015 ; Lawson et al, 2016 ), among others.…”
Section: Virtual Reality and Organizational Neurosciencementioning
confidence: 99%